Pengembangan Model Pembelajaran Bahasa Inggris Berbasis Audio Visual Content pada Perkuliahan Speaking for General Communication - fuad abdul Baqi; Achmad Hufad; John Pahamzah (Center of Language and Cultural Studies, 2023)
Technology-based learning models are needed in the current industrial era 4.0. Technological developments need to be implemented in the learning process. The combination of learning models with learning media is a necessity to be developed in English lectures. The development carried out is in the form of developing an English language learning model based on audio-visual content. This learning model focuses on projects in the form of audio-visual content. The type of research conducted is Research and Development (R & D) with the design of the ADDIE model development namely Analysis, Design, Development, Implementation and Evaluations. An audio-visual content-based English learning model was developed in the speaking for general communication course. The research instrument uses a validation sheet. Validation is carried out to material experts, educational technology, and learning evaluation using a scoring of likert scale. Data analysis techniques using qualitative descriptive statistics. The results of the study showed that the validation results of learning models, semester lesson plans, and speaking for general communication textbooks from validators consisting of educational technology experts, material experts and learning evaluation experts with interpretation criteria were very feasible. It can be concluded that the development of an audio-visual content-based English learning model is valid and appropriate to be used in the learning process of speaking for general communication.